Automation anxiety why and how to save work - Estlund, Cynthia (Oxford University Press, 2021)
This book confronts the hotly-debated prospect of mounting job losses from automation, and the divergent hopes and fears that prospect evokes, and proposes a strategy for mitigating the losses and spreading the gains from shrinking demand for human labor. Leading economists have concluded that automation is already exacerbating inequality by destroying more decent middle-skill jobs than it is creating. As ongoing innovations in artificial intelligence, machine learning, and robotics continue to chip away at the comparative advantages of human labor in a range of work tasks, those innovations are likely to yield growing job losses in the foreseeable future. Faced with this prospect, the book argues that we should set our collective sights on ensuring broad access to adequate incomes, more free time, and decent remunerative work even in a world with less of it. That will require not a single "magic bullet" solution like universal basic income or a federal job guarantee, but rather a multifaceted strategy centered on conserving, creating, and spreading work. The book elaborates that strategy in the U.S. context, but much of it is broadly relevant to other advanced economies. And while the proposed strategy is designed to address a foreseeable future of job scarcity, it will also help to rebalance lives already plagued by either too much work or not enough and to counter both economic inequality and racial stratification. The proposed strategy makes sense here and now, and especially as we face up to a future of less work"--